Answer:
x = 10, y = -8 (10,8)
Explanation:
Solve for x in the first equation
x = (74/9) - (2y/9)
replace all occurrences of x in 8x + 3y = 56 with 74/9 - 2y/9
8 ( 74/9 - 27/9) + 3y =56
Simplify the left side
(592 + 11y) / 9 = 56
Solve for y in the 2nd equation
multiply both sides of thye equation by 9
x= 74/9 - 2y/9
592 + 11y = 56 x (9)
Remove the parentheses x = 74/9 - 2y/9
592 +11y = 56 x (9)
Multiply 56 by 9
x = 74/9 - 2y/9
11 y = -88
Divide each term by 11 and simplify, x = 74/9 - (2(-8))/9 y = -8
Replace all occurrences of y in x = 74/9 - 2y/9 with -8
x= 74/9 - (2(-8)/9
x= 10
y= -8
Solution to the system of equations can be represented as a point (10,-8)